Designing media - Moggridge, Bill (MIT Press, 2010)
In Designing Media, Bill Moggridge examines connections and conflicts between old and new media, describing how the mainstream media have changed and how new patterns of media consumption are emerging. The book features interviews with thirty-seven significant figures in both traditional and new forms of mass communication. Accompanying DVD includes excerpts from all the interviews.